PENGARUH DIGITAL PARENTING PRESSURE TERHADAP SELF ESTEEM DAN PARENTING ANXIETY PADA IBU GENERASI Z DIKECAMATAN RAMBAH SAMO - Anelvi Novita Sari Novi; Desi Lestari; Indri Reskiana; Fatimah Azzahra (AflahConsilia : Jurnal Bimbingan dan Konseling, 2026)
The rapid development of digital technology has transformed parenting practices, particularly among Generation Z mothers who actively use social media as a source of parenting information. Although digital platforms provide various benefits, exposure to idealized parenting standards on social media may generate digital parenting pressure that affects mothers’ psychological well-being. This study aimed to examine the influence of digital parenting pressure on self-esteem and parenting anxiety among Generation Z mothers in Rambah Samo District, as well as to investigate the mediating role of self-esteem in this relationship. A quantitative approach with an explanatory survey design was employed involving 200 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using multiple regression and mediation analyses. The findings revealed that digital parenting pressure had a significant negative effect on self-esteem and a significant positive effect on parenting anxiety. Furthermore, self-esteem was found to mediate the relationship between digital parenting pressure and parenting anxiety. These findings highlight the importance of digital literacy and strengthening psychological resilience among young mothers in the digital era.